PENGELOLAAN ECOTOURISM KAYU PUTIH OLEH PEMERINTAH DESA KAWASEN KECAMATAN BANJARSARI KABUPATEN CIAMIS - Hana Lidia Rahmasari; Dini Yuliani; Regi Refian Garis (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This research is motivated by the not optimal management of ecotourism or eucalyptus nature tourism by the village government in Kawasen Village, Banjarsari District, Ciamis Regency. The purpose of this study was to determine the management of eucalyptus ecotourism by the government of Kawasen Village, Banjarsari District, Ciamis Regency. The research method used in this research is descriptive descriptive research method. Data collection techniques through observation, interviews, documentation and literature study. Data analysis techniques using data reduction, data presentation and drawing conclusions. Informants in this study amounted to 6 informants. The results showed that the Management of Kayu Putih Ecotourism by the Kawasen Village Government had not been carried out optimally, seen from the aspects of ecotourism management, namely tourist attraction, accessibility, tourist facilities and tourism institutions. This problem is caused by the village government's lack of effort in adding local culture to the Eucalyptus tourist attraction section, the lack of easy access to tourist sites such as the absence of social media promotions to support accessibility and access to tourist sites is still quite difficult, other problems related Incomplete tourist facilities, this is because the government has not attempted to build supporting facilities such as disabled-friendly facilities and places of worship due to limited budgets or funds. And also eucalyptus tourism managers who are still incompetent in terms of service, namely visitor administration because there has been no regular training from the village government or related agencies.